Leadership Qualities of the Islamic State Leaders Mixed with Quran, Hadith, and Contemporary Perspectives - Mina Manjurul Hossain Reza (Penerbit Hellow Pustaka, 2025)
Islamic leadership is not merely a position of power but a responsibility entrusted by Allah. It requires individuals with strong moral character, a deep understanding of Islamic principles, and a commitment to serving the community with justice, compassion, and wisdom. This study explained the key elements and attributes of Islamic concept of leadership in the light of guidelines provided by the Holy Quran and Prophet Hazrat Muhammad (PBUH), Caliphas, and the modern Islamic leaders. The essential characteristics of a good leader from an Islamic standpoint were also covered here, along with how modern state leaders might incorporate these qualities into their daily operations. The primary source of the information for this study is the Holy Quran's reputable verses, Hadith, books, and research articles that aid in fostering clarity in one's thoughts regarding many facets of the topic. The article reveals essential elements of Islamic leadership that contribute to fostering justice, accountability, and trust within society. This study additionally indicated that Islamic leadership integrates ethical integrity with social responsibility. By embodying these qualities, leaders can foster a sense of unity, trust, and progress within their communities.